Response of External Radiotherapy Alone in Stage IIB – IIIC Cervical Cancer Patients : Respon Radioterapi Eksterna Pasien Kanker Serviks Stadium IIB – IIIC - Wibowo, Antonius; Laihad, Bismarck J.; Mongan, Suzanna P.; Napitupulu, Enrico (Indonesian Journal of Obstetrics and Gynecology, 2022)
Objective: To investigate the therapeutic response and toxicity in cervical cancer patients with stage IIB-IIIC who undergo external radiation. Methods: This was a retrospective study using the medical records of the Obstetric Oncology and Radiotherapy Department at Prof. Dr. R. D. Kandou Hospital Manado. The research subjects were stage IIB-IIIC cervical cancer patients who underwent external radiation from September 2016 to December 2020. External radiation was administrated using 60Cobalt. The statistical analysis assessments in this study was carried out using descriptive analysis, while the analysis of the relationship was carried out using the Chi-Square method. The toxicity assessments were carried out from first day started external radiation up until 1 month after the therapy was deemed completed. Results : As many as 413 cervical cancer patients underwent external radiation during the study. However, only 192 cervical cancer patients with stage IIB-IIIC met the inclusion criteria in this study. The complete response to the therapy based on the findings was 65.6%, the partial response was 31.8%, the stable response was 1.6%, and the progressive response was 1%. In statistical analysis there was a significant association between cervical cancer stage and Overall Treatment Time with response to external radiotherapy. However, no significant association between tumor size and histopathological type with response to external radiotherapy. There were hematological toxicity (45.8%), skin toxicity (45.3%), gastrointestinal toxicity (6.3%) and urinary tract toxicity (2.6%). Conclusions: External radiotherapy response was a complete response where there was an association between cervical cancer stage and Overall Treatment Time with response to external radiotherapy, whereas there is no significant association found between the tumor size and histopathological type based on this research's findings. Most toxicity were hematology with complaints of anemia and thrombocytopenia Keywords: cervical cancer, external radiation response, toxicity. Abstrak Tujuan: Untuk mengetahui respon terapi dan efek samping pasien kanker serviks stadium IIB-IIIC yang menjalani radioterapi eksterna. Metode: Penelitian ini adalah penelitian deskriptif rektrospektif dengan menggunakan rekam medis Poli Onkologi Kandungan dan Instalasi Radioterapi RSUP Prof. Dr. R. D. Kandou Manado. Subyek penelitian adalah pasien kanker serviks stadium IIB-IIIC yang menjalani radiasi eksterna mulai September 2016 sampai Desember 2020. Radiasi eksterna dilakukan dengan sinar 60Cobalt. Penilaian analisis statistika pada penelitian ini menggunakan analisis deskriptif dan analisis hubungan menggunakan metode Chi Square. Penilaian efek samping dilakukan sejak hari pertama pasien memulai radiasi eksterna sampai 1 bulan setelah dinyatakan selesai menjalani radioterapi eksterna. Hasil: Selama periode penelitian didapatkan 413 pasien kanker serviks yang menjalani radiasi eksterna namun hanya 192 pasien kanker serviks stadium IIB-IIIC yang memenuhi kriteria inklusi pada penelitian ini. Respon terapi komplit sebesar 65,6%, respon terapi parsial sebesar 31,8%, respon terapi tidak berubah sebesar 1,6%, dan respon terapi progresif sebesar 1%. Pada analisis statistik terdapat hubungan bermakna stadium kanker serviks dan Overall Treatment Time dengan respon radioterapi eksterna, dan tidak terdapat hubungan bermakna ukuran tumor dan jenis histopatologi dengan respon radioterapi eksterna. Didapatkan efek samping hematologi (45,8%), efek samping kulit (45,3%), efek samping gastrointestinal (6,3%) dan efek samping traktus urinarius (2,6%). Kesimpulan: Respon radioterapi eksterna berupa complete response dimana terdapat hubungan bermakna antara stadium kanker serviks dan Overall Treatment Time dengan respon radioterapi eksterna. Tidak terdapat hubungan bermakna antara ukuran tumor dan jenis histopatologi. Efek samping terbanyak yaitu hematologi dengan keluhan berupa anemia dan trombositopenia. Kata kunci: efek samping, kanker serviks, respon radiasi eksterna.